Visitors’ loyalty towards Giant Panda Conservation Centre at Zoo Negara, Malaysia - Thoo, Poh Yee (2017)
Loyalty has been a major highlight in the tourism industry for being a crucial component to a sustainable business by ensuring a stable flow of visitors in future. It has always been a vital objective of service providers. Visitors are the main focus of any successful tourism business as the need to attract and retain visitors is definitely important to face the concept of quality, productivity, efficiency, growth and survival challenge in this field. Many studies of service quality have proven that these will lead to visitors’ satisfaction and results in visitors’ loyalty. However, many researchers have also identified that a satisfactory purchase experience is not enough to develop loyalty. Visitors’ positive memorable tourism experiences (MTEs) are also very crucial as it is proven to be a more potent driver of future behaviour such as loyalty. MTEs have recently emerged to become an important study for tourism destinations to compete in this rapid growing marketplace. Therefore, in order to create a visitors’ loyalty, bestowing visitors with great service quality and development of positive memorable tourism experiences (MTEs) are essential. Yet, there are currently lacks of studies regarding the relationship among these three dimensions. In conjunction with the sudden drop of total number of visitors in Zoo Negara Malaysia in the year 2015 even after the establishment of Giant Panda Conservation Centre (GPCC), it is crucial for GPCC, Zoo Negara to understand and gain loyal visitors since the giant pandas will be here for 10 years. Hence, the main objective of this research is to examine the factors that influence loyalty in relation to service quality and memorable tourism experience among visitors at GPCC in Zoo Negara. Moreover, this study is to close the theoretical gap by developing a model with these three dimensions which are still scarce in the literature. A quantitative research design was employed in this study. A self-administered survey was carried out with a sample of 217 visitors. A pilot survey was done to test the effectiveness of the questions in the instrument prior to the actual survey. Descriptive analysis and multiple regression analysis were used to analyse the data. The results showed that the visitors of GPCC have various socio-demographic and economic backgrounds. Overall, the visitors are positive of service quality, MTEs and loyalty towards GPCC. From the socio-demographic characteristics, visitors’ education level and gross monthly salary are found to affect the visitors’ loyalty.Lastly, the relationship among service quality, MTEs and loyalty had been determined and become clearer. Service quality and MTEs are indeed the antecedents of loyalty. In addition, MTEs has been found to mediate the relationship between service quality and loyalty with a full mediation which has helped to expand the current literature. In a nutshell, apart from providing a high quality of service, understanding the visitors’ MTEs is important when implementing segmentation and positioning strategies for a tourism destination as it will affect a visitor’s loyalty.